2019
DOI: 10.1242/dev.165589
|View full text |Cite
|
Sign up to set email alerts
|

Peri-arterial specification of vascular mural cells from naïve mesenchyme requires Notch signaling

Abstract: Mural cells (MCs) are essential for blood vessel stability and function; however, the mechanisms that regulate MC development remain incompletely understood, in particular those involved in MC specification. Here, we investigated the first steps of MC formation in zebrafish using transgenic reporters. Using pdgfrb and abcc9 reporters, we show that the onset of expression of abcc9, a pericyte marker in adult mice and zebrafish, occurs almost coincidentally with an increment in pdgfrb expression in peri-arterial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
98
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(108 citation statements)
references
References 56 publications
10
98
0
Order By: Relevance
“…Consistent with our results, vSMCs around the dorsal aorta have been traced back to cells derived from the sclerotome in zebrafish (50). In addition, mural cells in the zebrafish trunk vessels have been shown to be dependent on the mesoderm but not the neural crest lineage (57). Thus, blood vessel support cells in the zebrafish trunk, including perivascular fibroblasts and mural cells, likely originate from the sclerotome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with our results, vSMCs around the dorsal aorta have been traced back to cells derived from the sclerotome in zebrafish (50). In addition, mural cells in the zebrafish trunk vessels have been shown to be dependent on the mesoderm but not the neural crest lineage (57). Thus, blood vessel support cells in the zebrafish trunk, including perivascular fibroblasts and mural cells, likely originate from the sclerotome.…”
Section: Discussionmentioning
confidence: 99%
“…In the first scenario, all perivascular fibroblasts have the equal potential to differentiate into pericytes, but extrinsic cues determine which cell to switch on the pericyte fate. Notch signaling has been implicated in the regulation of pericyte formation in both mouse and zebrafish (57; 6063). In particular, recent work in zebrafish has shown that the activation of Notch signaling in naïve mesenchymal cells (likely corresponding to perivascular fibroblasts in our study) is crucial to induce pericyte differentiation around ISVs (Ando et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, imatinib (Gleevec) has been shown to improve BBB integrity caused by pericyte deficiency [20], and cilostazol/iloprost reduces pericyte detachment in an experimental stroke model in rat [168]. A complementary, although less high-throughput, model system for drug screening is zebrafish, where the combination of transparent embryogenesis and new fluorescent reporters to identify the various vascular cell types allows BBB function and other aspects of vascular biology to be monitored in vivo [173] (for review see ref. The study of BBB integrity in in vitro systems could clearly accelerate research and allow high-throughput screens to be conducted (for review see ref.…”
Section: Toward Therapy Developmentmentioning
confidence: 99%
“…Such three-dimensional tissue-mimicking systems may be better approximations of the in vivo situation than their two-dimensional counterparts, and it will be interesting to learn whether these systems will accelerate the discovery of therapeutic agents and provide new insights into mechanisms affecting BBB integrity. A complementary, although less high-throughput, model system for drug screening is zebrafish, where the combination of transparent embryogenesis and new fluorescent reporters to identify the various vascular cell types allows BBB function and other aspects of vascular biology to be monitored in vivo [173] (for review see ref. [174]).…”
Section: Toward Therapy Developmentmentioning
confidence: 99%
“…Further work has shown that Notch3 also has roles at earlier steps in the VSMC lineage, which are masked by partial redundancy with other Notch homologues. In zebrafish, Notch2 and Notch3 act together to regulate production during embryogenesis of both mesoderm-derived and neural crest-derived mural cells, the precursors of VSMCs [32]. A similar redundancy is found in mice as Notch2, Notch3 double mutants are embryo lethal with severe loss of VSMCs and vascular abnormalities [33].…”
Section: Developmental Roles Of Notch3mentioning
confidence: 88%